Recombinant tissue plasminogen activator in cases with fibrin formation after cataract surgery: a prospective randomised multicentre study. Issue 7 (1st July 1998) - Heiligenhaus, A; Steinmetz, B; Lapuente, R; Krallmann, P; Althaus, C; Steinkamp, W K; Dick, B
Abstract : AIMS: This study investigated the effect of tissue plasminogen activator (tPA) in patients with severe intracameral fibrin after extracapsular cataract extraction or phacoemulsification with posterior chamber intraocular lens implantation. METHODS: A randomised prospective multicentre study was carried out in 86 patients with intraocular fibrin formation 2–8 days after cataract surgery. While the first group (n=41) received only anti-inflammatory drugs, a single anterior chamber injection of tPA (10 μg) as an additional treatment to the standard was given in the second group (n=44). On days 1, 2, 14, and 90 after randomisation, the visual acuities, slit lamp findings, and intraocular pressures were documented in standardised protocols. Efficacy of treatment was judged by the rate of fibrinolysis (primary objective), the frequency of synechiae, and central capsular fibrosis (secondary objectives). RESULTS: The incidence and quantity of intraocular fibrin were significantly lower in the patients treated with tPA than in the control group (p<0.05). The frequencies of synechiae were reduced by tPA injection. The capsule fibrosis noted after 3 months was significantly lower in the tPA group (p=0.027). No ocular side effects were noted after the tPA injections. CONCLUSIONS: Lysis of postcataract fibrin formation is accelerated and increased by a single intracameral injection of 10 μg tPA in addition to standard anti-inflammatory treatment. The findings suggest that the tPA injection reduces posterior capsule fibrosis, which still has to be addressed in larger study populations and with a long term follow up.